A-to-I pre-mRNA editing in Drosophila is primarily involved in adult nervous system function and integrity. - Palladino, M.J.; Keegan, L.P.; O'Connell, M.A.; Reenan, R.A. (Cell, 2000)
Specific A-to-I RNA editing, like that seen in mammals, has been reported for several Drosophila ion channel genes. Drosophila possesses a candidate editing enzyme, dADAR. Here, we describe dADAR deletion mutants that lack ADAR activity in extracts. Correspondingly, all known Drosophila site-specific RNA editing (25 sites in three ion channel transcripts) is abolished. Adults lacking dADAR are morphologically wild-type but exhibit extreme behavioral deficits including temperature-sensitive paralysis, locomotor uncoordination, and tremors which increase in severity with age. Neurodegeneration accompanies the increase in phenotypic severity. Surprisingly, dADAR mutants are not short-lived. Thus, A-to-I editing of pre-mRNAs in Drosophila acts predominantly through nervous system targets to affect adult nervous system function, integrity, and behavior.